Metal Nanoparticles and Carbon-Based Nanostructures as Advanced Materials for Cathode Application in Dye-SensitizedSolar Cells. (12th April 2010) - Calandra, Pietro; Calogero, Giuseppe; Sinopoli, Alessandro; Gucciardi, Pietro Giuseppe
Abstract : We review the most advanced methods for the fabrication of cathodes for dye-sensitized solar cells employing nanostructured materials. The attention is focused on metal nanoparticles and nanostructured carbon, among which nanotubes and graphene, whose good catalytic properties make them ideal for the development of counter electrode substrates, transparent conducting oxide, and advanced catalyst materials.